Laelaspis nematii sp. nov. (Mesostigmata: Laelapidae) a new species of laelapid mites from southwest Iran - Arsalan Khalili-Moghadam (Persian Journal of Acarology)
A new species of the genus Laelaspis Berlese, L. nematii sp. nov. is described based on adult female specimens collected in association with Cataglyphis fritillariae Khalili-Moghadam et al., (Hymenoptera: Formicidae) in Koohrang county (Dashte laleh), Chaharmahal va Bakhtiari Province, southwestern Iran.